Evaluation of Failed ACL Reconstruction: An Updated Review - Kemler B; Coladonato C; Sonnier JH; Campbell MP; Darius D; Erickson BJ; Tjoumakaris FP; Freedman KB (Dove Medical Press, 2024)
Bryson Kemler,1 Carlo Coladonato,1 John Hayden Sonnier,1 Michael P Campbell,1 Danielle Darius,2 Brandon J Erickson,1 Fotios Paul Tjoumakaris,1 Kevin B Freedman1 1Department of Orthopaedic Surgery, Rothman Institute, Philadelphia, PA, USA; 2Department of Education, Drexel University College of Medicine, Philadelphia, PA, USACorrespondence: Kevin B Freedman, Rothman Orthopaedics at Thomas Jefferson University, 825 Old Lancaster Road, Suite 200, Bryn Mawr, Philadelphia, PA, 19010, USA, Email Kevin.Freedman@rothmanortho.comAbstract: Failure rates among primary Anterior Cruciate Ligament Reconstruction (ACLR) range from 3.2% to 11.1%. Recently, there has been increased focus on surgical and anatomic considerations which predispose patients to failure, including excessive posterior tibial slope (PTS), unaddressed high-grade pivot shift, and improper tunnel placement. The purpose of this review was to provide a current summary and analysis of the literature regarding patient-related and technical factors surrounding revision ACLR, rehabilitation considerations, overall outcomes and return to sport (RTS) for patients who undergo revision ACLR. There is a convincingly higher re-tear and revision rate in patients who undergo ACLR with allograft than autograft, especially amongst the young, athletic population. Unrecognized Posterior Cruciate Ligament (PLC) injury is a common cause of ACLR failure and current literature suggests concurrent operative management of high-grade PLC injuries. Given the high rates of revision surgery in young active patients who return to pivoting sports, the authors recommend strong consideration of a combined ACLR + Anterolateral Ligament (ALL) or Lateral extra-articular tenodesis (LET) procedure in this population. Excessive PTS has been identified as an independent risk factor for ACL graft failure. Careful consideration of patient-specific factors such as age and activity level may influence the success of ACL reconstruction. Additional technical considerations including graft choice and fixation method, tunnel position, evaluation of concomitant posterolateral corner and high-grade pivot shift injuries, and the role of excessive posterior tibial slope may play a significant role in preventing failure.Keywords: ACL, anterior cruciate ligament, anterior cruciate ligament reconstruction, failed ACL graft, posterior tibial slope, revision ACL reconstruction